Caracterização das Metaloproteinases de Matriz- 2 e -9 circulantes com o nível de atividade física e os efeitos do treino aeróbio em indivíduos pós-acidente vascular cerebral em fase crônica - Garcia-Salazar, Luisa Fernanda (2022)
High concentrations of matrix metalloproteinases-2 (MMP-2) and -9 (MMP-9) are associated with inflammation shortly after stroke and functional prognosis. It is proposed that during the chronic phase, post-stroke individuals exhibit a systemic inflammatory state that may be related to comorbidities. On the other hand, the muscular characteristics of this population are associated with the release of some cytokines that may enhance systemic inflammation, such as interleukin-6 and -10. The inclusion of aerobic exercises (AE) in the rehabilitation programs of these individuals has been suggested as an important strategy for recovery. AE improves mobility, cardiopulmonary conditions, cognition, regulates cardiovascular risk factors in these individuals, and has been associated with neuroplasticity, therefore motor recovery due to the increased concentration of Brain Derived Neurotrophic Factor (BDNF) mediated by the myokine Irisin. In this context, two studies were developed in this thesis, the first one aimed to quantify the serum activity of MMP-2 and MMP-9 in chronic post-stroke individuals and correlate these gelatinases with variables of physical activity level, body composition, functional capacity, and walking test, as well as with metabolic and inflammatory biomarkers. In addition, the activity of these gelatinases was characterized according to the motor impairment of these individuals. The second study, evaluated the changes in gelatinases activity in serum samples from chronic post-stroke subjects who received an intervention protocol for two-week, consisting of one session of high-intensity interval EA before the modified constraint-induced movement therapy (mCIMT). We also correlated the gelatinases with BDNF and Irisin concentrations, and with changes in manual dexterity and functional capacity. It was demonstrated with these studies that chronic post-stroke individuals have increased MMP-9 activity when compared to healthy individuals. Positive correlations were observed with time and steps at low cadence and negative correlations with medium cadence and peak activity index. According to motor impairment, MMP-2 activity is increased in the mild-moderate group compared to the control group. Furthermore, it was observed that the intervention protocol with the inclusion of AE, produces an acute response in MMP-9 increasing its activity. This increase was not correlated with manual dexterity nor with the functional capacity of these individuals, and there was also no relationship with BDNF and Irisin concentration. In conclusion, chronic post-stroke individuals present altered MMP-2 and -9 activity indicating a possible systemic inflammation, associated with the cardiovascular conditions of these individuals. In addition to showing, before an acute intervention, an increase in MMP-9 activity indicates a possible adaptive process prior to the modifications of vessels and muscle tissue to the AE. For long-term modifications in cardiovascular and/or muscular conditions, a change in the physical activity level of these individuals or the execution of longer duration intervention programs would be necessary.